Safeguarding village funds: Strategies to prevent corruption - Satya Fauziah; Abdul Halim; Evi Maria (The Indonesian Accounting Review, 2024)
The rampant cases of village fund corruption in Malang Regency have resulted in the main purpose of village funds, which should be allocated for village development and community empowerment, not being able to run as expected. This study aims to obtain an overview and understanding related to the preparation and implementation of village fund corruption prevention strategies by the Regional Inspectorate of Malang Regency. In addition, this study also aims to analyze the causal factors for the ongoing occurrence of village fund corruption cases even though the Regional Inspectorate has prepared and implemented corruption prevention strategies. This qualitative study uses a case study approach. The results of this study indicate that there are two types of village fund corruption prevention strategies implemented by the Regional Inspectorate: ex-ante control strategy and ex-post control strategy. The imbalance in the implementation of the two strategies causes the strategies that have been implemented to not be fully able to minimize the factors that cause village fund corruption. These factors include pressure, opportunity, rationalization, integrity, capability, arrogance, and the culture in village head elections. This study is expected to provide input related to the implementation of village fund corruption prevention strategies in Malang Regency.